Development of Photo Spot at Madasari Beach Masawah Village Cimerak Sub-District - Amelia, Widya; Azahra, Tiara; Lugina, Sukma; Nurlaela M, Siti; N S, Ratu Tria; Nabillatuzahra, Nabillatuzahra; Abdulloh N, Jajang; Adelia, Gita; Martadiraja, Frazia; Mubarok, Fariz; Akbar N, Dimas; Via, Dede; Nurul H, Aima; A R, Zanzani; Suhartini, Titin (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Every community needs self-awareness in building the development of a tourist village (Madasari Hamlet) in Masawah Village, Cimerak District. Collecting data about problems in this hamlet through interviews, observation, and documentation.